포도전정가지 추출물이 UVB에 유도된 피부 손상에 대한 알레르기와 피부증식 억제효과 - 김정희; Joung-hee Kim; 김대환; Dae Hwan Kim; 김극준; Keuk-jun Kim (Korean journal of clinical laboratory science, 2017)
본 연구는 포도수확 후 버려지는 가지를 이용한 포도전정가지 추출물(grape pruning stem extracts, GPSE)에 함유된 polyphenol류가 UVB로 유도된 HR-1 hairless mice의 손상된 피부에 대한 피부증식 억제, 항 알레르기, 아포토시스 억제능을 분석하여 기능성 화장품 소재로서의 응용 가능성을 확인하고자 하였다. 포도전정가지에서 polyphenol 성분을 80% 에탄올로 추출하고 여과하여 농축한 후, 동결건조하여 -20°C에 보관하면서 사용하였다. GPSE의 유효성분 함량은 HPLC를 사용하여 선행연구논문에 보고하였다. 피부손상을 유도하기 위해 UVB를 HR-1 hairless mice에 조사하였고, GPSE가 피부 알레르기 반응을 일으키는지 확인하기 위하여 toluidine blue 염색을 통하여 비만세포의 수를 확인한 결과 포도전정가지 추출물(GPSE)를 도포한 그룹에서는 정상군과 유사한 결과를 나타내어 GPSE 도포군은 알레르기 반응이 없으며 suncream 대조군대비 현저하게 감소하는 것을 확인할 수 있었다. 표피의 증식표지자인 PCNA 면역조직화학적 염색을 시행한 결과 GPSE와 serum base 혼합물의 모든 농도에서 대조군 대비 평균 42%로 표피상피세포 증식 억제 효과를 나타내었다. 또한 GPSE와 serum base 혼합물이 자외선 조사로 인한 아포토시스 억제율은 대조군 대비 평균 27% 억제 한다는 것을 알 수 있었다. 이상의 결과로 포도전정가지로부터 추출한 페놀성 화합물이 화장품기초 원료인 serum base에 함유토록 제조된 GPSE는 피부증식억제, 알레르기 억제, 아포토시스 억제효과를 얻을 수 있었다. 본 연구의 의의는 지역포도농가에서 수확 후 버려지는 포도전정가지에서 폴리페놀류와 같은 유효성분을 확보하여 고부가가치를 창출할 수 있는 기능성화장품 원료로서의 활용 가치가 높을 것으로 기대된다. This study examined the effects of polyphenols in grape pruning stem extracts (GPSE) using grape stems discarded after harvest. The inhibitory effects on allergy, proliferation, and apoptosis in UVB-induced HR-1 hairless mice were analyzed. The applicability as a material for functional food and functional cosmetics was evaluated. The contents of the active ingredients of GPSE were analyzed by HPLC. After UVB irradiation on the dermis of HR-1 hairless mice, the number of mast cells was determined by toluidine blue staining to confirm that the skin allergic reaction was caused by GPSE. The results were similar to the normal group in the group applied GPSE, and there was no allergic reaction in the GPSE application group and a significant decreased compared to the sun cream control. PCNA immunohistochemical staining of the epidermal proliferation factor had an inhibitory effect on epidermal epithelial cell proliferation in all concentrations of GPSE and serum base mixture as an average of 42% compared to the control group. The mixture of GPSE and serum base suppressed the apoptosis inhibition rate by 27% on average compared to the control. These results confirmed the inhibitory effects GPSE on the allergic, proliferation, and apoptosis activities by with a serum base on UVB-induced skin damage. GPSE is a functional ingredient with potential skin protection effects, and has a high utilization as an ingredient for functional cosmetics.